First record of Hydrolagus affinis (Holocephali: Chimaeriformes: Chimaeridae) from Madeira and the Seine Seamount (North Atlantic Ocean) - M. Freitas; A.J. Almeida; J. Delgado; J.A. González; J.I. Santana; M. Biscoito (Acta Ichthyologica et Piscatoria, 2011)
The smalleyed rabbitfish, Hydrolagus affinis (de Brito Capello, 1868) (Chimaeridae), is recorded from the archipelago of Madeira for the first time, based on seven specimens caught between 1200 and 2500 m depth. This record extends the previously known range of distribution of this species, and also confirms its vertical distribution down to 2500 m. Additional material collected from the Canary Islands and the Azores was used for comparison.